Supervisory Control Scheme of a Wind Farm Connected to a Hybrid Microgrid. (3rd October 2022) - Benghanem, Mustapha; AlKassem, Abdulrahmane; Bensaber, Abdelhaq Amar; Draou, Azeddine
Abstract : Nowadays, the generation of wind power combined with a battery energy storage system offers a viable solution for electricity supply to isolated areas with no access to the grid. However, the speed of the wind is unpredictable and the inherent nonlinearities of the wind turbine and generator system cause fluctuations in the voltage, power, and frequency. This paper proposes a new three-layered control technique applied to a wind farm that uses doubly-fed induction generators (DFIGs) connected to a remote hybrid microgrid. The first layer provides local control to each DFIG wind turbine based on a nonlinear and robust control strategy. The second layer coordinates and controls the flow of power between the turbine and the storage system to make sure that load demand is being satisfied and the desired limits of the state of charge are respected. Finally, and in the third layer, we implement a supervisory controller that will be responsible for the generation of the references for the active power as per the load demand. The proposed off-grid wind power system and battery storage and its three-layer hierarchical control scheme are simulated under MATLAB/Simulink environment and tested under various load and speed profiles. Through the numerous test data obtained, it has been shown that the control strategy under study is robust and effective.